2021
DOI: 10.1163/1568539x-bja10069
|View full text |Cite
|
Sign up to set email alerts
|

The role of touch in captive and semi-captive Antillean manatees (Trichechus manatus manatus)

Abstract: Tactile signals have been neglected in aquatic animal studies despite being a major communication modality. We investigated Antillean manatees’ tactile behavioural repertoire and budget in captivity (7-females and 4-males) and semi-captivity (4-males) in Brazil. We detected 17 tactile behaviours (14.03% of the activity budget) with social, self-maintenance, or environmental exploration functions. The observation method influenced the detection of self-maintenance behaviours — focal animal and ad libitum detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…Since manatees have extra sensitivity in tactile sensory systems, the objects introduced in their pool might be better detected because of the movement of the water they generate, which may explain why manatees displayed more reactions for the floating and submerged objects. Similarly to our study, Antillean manatees have been observed frequently interacting with coconuts floating above the water in rehabilitation pools (Lucchini et al, 2021). In our study, individuals were habituated to the presence of grass, other species, and humans around their pool, and were exposed to various types of sounds linked to anthropogenic activities or other species in their environment.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Since manatees have extra sensitivity in tactile sensory systems, the objects introduced in their pool might be better detected because of the movement of the water they generate, which may explain why manatees displayed more reactions for the floating and submerged objects. Similarly to our study, Antillean manatees have been observed frequently interacting with coconuts floating above the water in rehabilitation pools (Lucchini et al, 2021). In our study, individuals were habituated to the presence of grass, other species, and humans around their pool, and were exposed to various types of sounds linked to anthropogenic activities or other species in their environment.…”
Section: Discussionsupporting
confidence: 85%
“…Also, manatees frequently interacted with keepers diving in their pool and might have learned to pay attention to submerged items. Some studies emphasized that the vibrissae present over the entire body are a major source of sensation (Bauer & Reep, 2018; Lucchini et al, 2021). Indeed, manatees are able to discriminate precisely between different object textures and also detect small water movements (Bauer et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations